Prolonged jaundice evaluation opens a can of worms - Kumar, Karishmah Senthil; Muthusamy, Sahana; Senthil, Radhalakshmi (International Journal of Contemporary Pediatrics, 2025)
We present a case of a second-born male from a non-consanguineous marriage who exhibited prolonged jaundice. Upon clinical evaluation, he was found to have bilateral cryptorchidism and a micropenis. Further investigation revealed the presence of hypothyroidism. Due to the presence of abnormal genitalia and hypothyroidism, a comprehensive endocrine assessment was conducted, which identified deficiencies in multiple pituitary hormones. Genetic testing, prompted by persistent growth failure, confirmed a diagnosis of Culler-Jones syndrome (CJS) - a rare autosomal dominant disorder characterized by hypopituitarism, postaxial polydactyly and distinct facial abnormalities, including hypotelorism, cleft lip and palate, a flat nose and midfacial hypoplasia. This condition is caused by a heterozygous mutation in the GLI2 gene on chromosome 2q14.2. The phenotype of CJS is highly variable, demonstrating both incomplete penetrance and variable expressivity. In our case, the infant presented with combined pituitary hormone deficiency, an absent anterior pituitary gland, an ectopic posterior pituitary, significant growth retardation and underdeveloped genitalia. GLI2 mutations should be suspected in patients with congenital hypopituitarism, persistent growth failure (with or without abnormal facies) and polydactyly. Genetic testing is crucial for early diagnosis, as it facilitates better management, improves outcomes and helps anticipate the disease course.